Acquired disorders of mitochondrial metabolism and dynamics in pulmonary arterial hypertension - Breault, Nolan M.; Wu, Danchen; Dasgupta, Asish; Chen, Kuang-Hueih; Archer, Stephen L. (Frontiers in Cell and Developmental Biology, 2023)
Pulmonary arterial hypertension (PAH) is an orphan disease of the cardiopulmonary unit that reflects an obstructive pulmonary vasculopathy and presents with hypertrophy, inflammation, fibrosis, and ultimately failure of the right ventricle (RVF). Despite treatment using pulmonary hypertension (PH)-targeted therapies, persistent functional impairment reduces the quality of life for people with PAH and death from RVF occurs in approximately 40% of patients within 5 years of diagnosis. PH-targeted therapeutics are primarily vasodilators and none, alone or in combination, are curative. This highlights a need to therapeutically explore molecular targets in other pathways that are involved in the pathogenesis of PAH. Several candidate pathways in PAH involve acquired mitochondrial dysfunction. These mitochondrial disorders include: 1) a shift in metabolism related to increased expression of pyruvate dehydrogenase kinase and pyruvate kinase, which together increase uncoupled glycolysis (Warburg metabolism); 2) disruption of oxygen-sensing related to increased expression of hypoxia-inducible factor 1α, resulting in a state of pseudohypoxia; 3) altered mitochondrial calcium homeostasis related to impaired function of the mitochondrial calcium uniporter complex, which elevates cytosolic calcium and reduces intramitochondrial calcium; and 4) abnormal mitochondrial dynamics related to increased expression of dynamin-related protein 1 and its binding partners, such as mitochondrial dynamics proteins of 49 kDa and 51 kDa, and depressed expression of mitofusin 2, resulting in increased mitotic fission. These acquired mitochondrial abnormalities increase proliferation and impair apoptosis in most pulmonary vascular cells (including endothelial cells, smooth muscle cells and fibroblasts). In the RV, Warburg metabolism and induction of glutaminolysis impairs bioenergetics and promotes hypokinesis, hypertrophy, and fibrosis. This review will explore our current knowledge of the causes and consequences of disordered mitochondrial function in PAH.